The Effect of Different Resistance Training Protocols on Cardiac Autonomic Modulation During Exercise Recovery: A Crossover, Randomized, and Controlled Pilot Study - Helyel Rodrigues Gobbo; Gabriel Marcelino Barbosa; Lucas Cezar de Oliveira; Gustavo Vieira de Oliveira (Journal of Vascular Diseases)
Purpose: This study investigated the impact of two different resistance training (RT) protocols on cardiac autonomic modulation during exercise recovery in trained individuals. It was hypothesized that a hypertrophic resistance training program would induce more significant stress and negatively affect cardiac autonomic modulation compared to a power/force resistance training program. Methods: Six healthy, trained participants (aged 18–40) were randomized in a crossover and controlled pilot study. Participants performed two RT protocols: (i) three sets of 10 repetitions with 85% of 10 RM, 60 s inter-set rest (3x1060s) and (ii) eight sets of three repetitions with 85% of 3 RM, 120 s inter-set rest (8x3120s). Heart rate variability (HRV) was measured before and 30 min after each RT session. Results: Significant reductions in HRV parameters (RMSSD, HF, and SD1) were observed following the 3x1060s protocol (hypertrophic design) compared to baseline. Conversely, the 8x3120s (power/force design) protocol did not show significant changes in HRV parameters. A significant interaction effect for time and RT protocol was found for all HRV measures with more significant reductions observed after 3x1060s compared to 8x3120s. Conclusions: The hypertrophic RT session (3x1060s) significantly reduced HRV parameters, suggesting higher physiological stress and potentially negative implications for cardiac autonomic recovery than the power/force RT session (8x3120s). These findings highlight the importance of considering exercise intensity and protocol design to manage cardiac autonomic stress during resistance training.